EXPERIMENTAL STUDIES ON CONGO RED ADSORPTION BY TEA WASTE IN THE PRESENCE OF SILICA AND Fe2O3 NANOPARTICLES - Alireza Shojamoradi; Hosein Abolghasemi; Mohammad Esmaili; Mohammad Foroughi-dahr; Hooman Fatoorechi (Journal of Petroleum Science and Technology, 2013)
In this work, the adsorption of the anionic dye, Congo red (CR), from aqueous solution by using tea waste (TW) has been carried out at 30 °C. The equilibrium sorption isotherms and kinetics were investigated. The equilibrium adsorption was studied by the Langmuir and Freundlich models of adsorption. The experimental results manifested that the Langmuir isotherm was the best model for the adsorption of CR by TW and implied the monolayer adsorption of CR on TW with the adsorption capacity of 40.6 mg/g at 30 °C. The kinetic data resulted from batch experiments were analyzed using pseudo-first-order and pseudo-second-order models. It was found that pseudo-second-order model provided the best fit for the experimental data (R2>0.99). The results illustrated that both silica and Fe2O3 nanoparticles increased the adsorption of CR on TW by about 5% and 10% at 30 °C, respectively. The results suggested that TW should be a potential low-cost adsorbent for the removal of CR from aqueous solution.